2010
DOI: 10.1126/scitranslmed.3001510
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Differentiates Rapidly from Slowly Progressing Forms of Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis is a generally progressive disorder with highly heterogeneous disease progression. The most common of the idiopathic interstitial pneumonias, idiopathic pulmonary fibrosis is characterized by a steady worsening of lung function and gas exchange cause by diffuse alveolar damage and severe fibrosis. We examined clinical features of patients with idiopathic pulmonary fibrosis to classify them as exhibiting rapid or slowly progressive over the first year of follow-up. We identified di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 59 publications
6
152
0
Order By: Relevance
“…Therefore, TLRs has been proposed to regulate pulmonary fibrosis by sensing alveolar epithelial cell damage. Consistent with this suggestion, several studies have shown that TLRs expressed in lung tissues regulate pulmonary fibrosis (11)(12)(13)(14).…”
supporting
confidence: 50%
“…Therefore, TLRs has been proposed to regulate pulmonary fibrosis by sensing alveolar epithelial cell damage. Consistent with this suggestion, several studies have shown that TLRs expressed in lung tissues regulate pulmonary fibrosis (11)(12)(13)(14).…”
supporting
confidence: 50%
“…Moreover, it has been reported that deficiency of MyD88, the common adaptor for all TLRs except TLR-3, protects mice from inflammation and fibrosis (51). In contrast to TLR-2 and TLR-4, TLR-9 appears to promote lung fibrosis (52). Those results were confirmed by another study, in which TLR-4 deficient mice exhibited a significant reduction in fibroblast accumulation and renal fibrosis (53).…”
Section: Tlrs and Drug-induced Gingival Overgrowthsupporting
confidence: 78%
“…11,19,20,22,44 Although ample evidence has accrued to strongly suggest that idiopathic pulmonary fibrosis originates with epithelial dysfunction, the pathological fibroblast from IPF patients has undergone durable reprogramming in the form of epigenetic modifications, as exemplified by the capacity of adoptively transplanted human IPF pathological fibroblasts to recapitulate lung disease in immunodeficient mice. 98 It is imperative that future studies focus on the epigenetic changes that could be modified to reduce myofibroblast differentiation and overactivated cell survival pathways.…”
Section: Fibroblasts As Therapeutic Targetsmentioning
confidence: 99%